Self-Understanding of the Crisis in the Humanities against the “Invasive” Instrumental Rationality - LOŠONC, Alpar (Anafora, 2023)
The paper consists of three parts together with the introduction and conclusion. The first part considered the humanities in the perspective of humanization and explains why the interpretation of its crisis is not self-evident. The symptoms of the crisis are treated on the basis of self-understanding of selected actors thematizing such phenomena as is the situation in education, as well as the constellation of certain forms of knowledge that are indispensable in terms of political framing of democratization. The axis of crisis self-interpretations presents itself by the fact that it features a hegemonic form of economic rationality which “invasively” transforms the framework of the humanities. How can the humanities react to the situation? The second part seeks to answer this very question: what forms of reflexivity can be developed in order to resist the mentioned hegemony? The humanities contain idiosyncratic potentials that enable them to dissolve the ruling ideologies in terms of instrumental rationality and utilitarianism. “Economic humanities” are a form of reflection for the humanities that confronts the mentioned hegemony. The third part contextualizes the crisis-determined humanities through historical dynamics of abstraction and shows why the humanities care about reflecting on the modern finalization of abstraction on the occasion of humanization. Finally, the paper argues that, although the current expansion of abstraction affects the humanities, the crisis implies the existence of a space of possibility in which indecision exists.